(3GdeQLY aj GdJacjQ GdGSJQGJjLj hGdGOGQI GdGSJQGJjLjIs - (3CHh HcQ(B, (3eUWaj eMehOs ((3GdGScfOQjIs (3GdOGQ GdLGeYjIs, 2004)
(3GdGWGQ GdYGe ddGOGQI GdGSJQGJjLjI hfXGe GdJNWjW GdGSJQGJjLj, GdJacjQ GdGSJQGJjLj hGdGOGQI GdGSJQGJjLjI, OQGSI GdHjFI GdOGNdjI ddefXeI heeGQSI GdGOGQI ddGSJQGJjLjI, OQGSI hJMdjd GdHjFI GdNGQLjI, eeGQSI GdGOGQI GdGSJQGJjLjI, QSGdI GdefXeI, GdCgOGa GdGSJQGJjLjI, GdaQVjGJ GdGSJQGJjLjI, GdGSJQGJjLjGJ, GSJQGJjLjGJ GdhXGFa (B((3GdHOGFd GdGSJQGJjLjI Ydi eSJhi GdhXGFa(B)(3, eQGLYI GdGSJQGJjLjGJ hJfajPgG(B.s
Keywords: (3EOGQI GdCYeGds; (3GdESJQGJjLjIs; (3GdJNWjWs